Inhibition of ALDH2 protects PC12 cells against formaldehyde‐induced cytotoxicity: involving the protection of hydrogen sulphide. (May 2017) - Chen, Ying; Zhou, Cheng‐Fang; Xiao, Fan; Huang, Hong‐Lin; Zhang, Ping; Gu, Hong‐Feng; Tang, Xiao‐Qing
Summary: Formaldehyde (FA), a common environmental contaminant, has toxic effects on the central nervous system (CNS). We have previously found that hydrogen sulphide (H2 S), the third endogenous gaseous mediator, protects neuron against the toxicity of FA. However, the underlying mechanism is poor. Aldehyde‐dehydrogenase‐2 (ALDH2) plays a major role in detoxification of reactive aldehyde in a range of organs and cell types. Therefore, we speculated that H2 S antagonizes FA‐induced neurotoxicity by modulating ALDH2. In the present study, we found that the exposure of PC12 cells to FA causes increase in ALDH2 expression and activity. Daidzin, an inhibitor of ALDH2, significantly antagonizes FA‐exerted cytotoxicity and oxidative stress including the accumulation of intracellular reactive oxygen species (ROS), 4‐hydroxy‐2‐trans‐nonenal (4‐HNE), and malondialdehyde (MDA), in PC12 cells. We also showed that daidzin markedly attenuated FA‐induced apoptosis in PC12 cells. Furthermore, we found that H2 S reverses FA‐elicited upregulation of ALDH2 in PC12 cells. Our results demonstrated the involvement of downregulation of ALDH2 in the protection of H2 S against FA neurotoxicity.